Bioprospecting of Beneficial Bacteria Traits Associated With Tomato Root in Greenhouse Environment Reveals That Sampling Sites Impact More Than the Root Compartment - Anzalone, Alice; Di Guardo, Mario; Bella, Patrizia; Ghadamgahi, Farideh; Dimaria, Giulio; Zago, Rosario; Cirvilleri, Gabriella; Catara, Vittoria (Frontiers in Plant Science, 2021)
Tomato is subject to several diseases that affect both field- and greenhouse-grown crops. To select cost-effective potential biocontrol agents, we used laboratory throughput screening to identify bacterial strains with versatile characteristics suitable for multipurpose uses. The natural diversity of tomato root associated bacterial communities was bioprospected under a real-word environment represented by an intensive tomato cultivation area characterized by extra-seasonal productions in the greenhouse. Approximately 400 tomato root associated bacterial isolates, in majority Gram-negative bacteria, were isolated from three compartments: the soil close to the root surface (rhizosphere, R), the root surface (rhizoplane, RP), and the root interior (endorhizosphere, E). A total of 33% of the isolates produced siderophores, and were able to solubilise phosphates and grow on NA with 8% NaCl. A total of 30% of the root-associated bacteria showed antagonistic activity against all the tomato pathogens tested, i.e. Clavibacter michiganesis pv. michiganensis, Pseudomonas syringae pv. tomato, P. corrugata and Xanthomonas euvesicatoria pv. perforans and Fusarium oxysporum f. sp. lycopersici. We found that the sampling site rather than the root compartment of isolation influenced bacterial composition in terms of analysed phenotype. This was demonstrated through a diversity analysis including general characteristics and PGPR traits, as well as biocontrol activity in vitro. Analysis of 16S rRNA gene (rDNA) sequencing of 77 culturable endophityc bacteria that shared multiple beneficial activity revealed a predominance of bacteria in Bacillales, Enterobacteriales, and Pseudomonadales. Their in vitro antagonistic activity showed that Bacillus spp. were significantly more active than the isolates in the other taxonomic group. In planta activity against phytopathogenic bacteria of a subset of Bacillus and Pseudomonas isolates was also assessed.